Glycyrrhizin Inhibits Interleukin-8 Production and Nuclear Factor-κ B Activity in Lung Epithelial Cells, but Not Through Glucocorticoid Receptors - Hironori Takei; Yuichiro Baba; Akinori Hisatsune; Hiroshi Katsuki; Takeshi Miyata; Kazumi Yokomizo; Yoichiro Isohama (Elsevier, 2008)
This study was designed to examine the glucocorticoid-like inhibitory effect of glycyrrhizin (GL) on interleukin (IL)-8 production in A549 lung epithelial cells. GL, as well as dexamethasone (DEX) inhibited both tumor necrosis factor (TNF)-α -and IL-1β -induced IL-8 production, mRNA expression, and promoter activity in A549 cells. Both GL and DEX inhibited transactivation of nuclear factor (NF)-κ B, without inhibiting translocation of the NF-κ B p65 subunit to the nucleus. However, the effect of GL was insensitive to RU486, a GR antagonist, and to GR knockdown by siRNA. Furthermore, only GL inhibited DNA binding of p65 to the IL-8 promoter region. These findings indicated that GL had a glucocorticoid-like inhibitory effect on IL-8 production via a mechanism that differs from that of glucocorticoids. Keywords:: glycyrrhizin, glucocorticoid, nuclear factor (NF)-κ B, interleukin (IL)-8, A549 cell